Comparison of pelvic and para-aortic lymphadenectomy versus para-aortic lymphadenectomy alone for locally advanced FIGO stage IB2 to IIB cervical cancer using a propensity score matching analysis: Results from the FRANCOGYN study group. Issue 12 (December 2018) - Bendifallah, Sofiane; de Foucher, Tiphaine; Ouldamer, Lobna; Bricou, Alexandre; Lavoue, Vincent; Varinot, Justine; Canlorbe, Geoffroy; Carcopino, Xavier; Raimond, Emilie; Huguet, Florence; Graesslin, Olivier; Touboul, Cyril; et al.
Abstract: Introduction: Pre-treatment evaluation of nodal status is crucial in women presenting with locally advanced cervical cancer (LACC). However, the prognostic impact of surgical staging remains to be proved, as published results comparing surgical versus radiological staging are contradictory. The aim of this study was to compare the prognosis of women with FIGO stage IB2–IIB CC who underwent surgical nodal staging including either exclusive para-aortic lymphadenectomy (PAL) or comprehensive pelvic + para-aortic lymphadenectomy (P-PAL). Materials and methods: Data of 314 women with FIGO stage IB2 to IIB CC treated between January 2000 and January 2015 were retrospectively abstracted from nine French institutions. The prognosis and outcomes were compared by Propensity score (PS) matching (PSM) analysis. Results: The median follow-up was 33 months (2–114). When comparing women who underwent PAL vs P-PAL, the recurrence rates were 26% (37/144) and 28% (41/144), respectively (p = 0.595). The respective 3-year recurrence free survival (RFS) for P-PAL and PAL were 72.9% (95% CI, 65.7–81.0) and 70.7% (95% CI, 62.4–80.2), (p = 0.394). The respective 3-year overall survival (OS) rates for P-PAL and PAL were 86.8% (95% CI, 81.1–92.9) and 78.6% (95% CI, 70.4–87.7) (p = 0.592). In the sub-group of women with lymph node metastases, RFS was improved for women who underwent P-PAL compared to those with exclusive PAL (p = 0.027), with no difference in OS (p = 0.187). Conclusions: Comprehensive P-PAL does not seem to be of significant therapeutic benefit compared to exclusive PAL.